Pelatihan Virtual Reality untuk Branding Sekolah di Era Digital - Angga, Pratama; Widodo, Edi; Winarti, Titin (Redtech Putra Benua, 2024)
This training program aims to enhance the skills of students at SMK Kristen Surakarta in utilizing Virtual Reality (VR) technology to support school branding. The program was designed to provide an in-depth understanding of how VR can be used as an innovative and effective promotional tool. The training involved 27 students from grades X to XII, with pretest and posttest participation from 21 and 18 respondents, respectively. The results showed an increase in understanding of VR integration for promotional media from 20% to 94%. Additionally, 96% of participants demonstrated improved critical thinking skills in utilizing VR technology for school branding. These findings indicate that the training successfully enhanced participants' skills and understanding in effectively leveraging VR.